PENDAMPINGAN PENGURUS MASJID DALAM UPAYA REKTIFIKASI ARAH KIBLAT DI PROVINSI RIAU - Sofia hardani hardani (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
ABSTRACT Evil is an act committed by a person or group of persons whose nature harms others. At this time the crimes are much developed either in the form of Corruption, Narcotics or other crimes. Along with the level of crime, the Government seeks to do the prevention and eradication with the rules of law to overcome it. Then from that writer do research about Stipulation of Money Result Of Crime In Business Investment Activity, this arise from writer observation either through mass media, development of crime rate of various forms lost the origin of crime in good way in the form of activity of Business Investment, join in Capital Market etc. Of these problems was born Law No. 15 of 2002, Law No. 25 of 2003, and Law No. 8 of 2010 on Prevention and Eradication of Money Laundering Crime.This type of research is in the form of normative juridical based on data secondary and supported by juridical historical and juridical approach of comparative. The regulation of prevention and eradication of crime of Crime in Business Investment activity has been changed will change the level of corruption, Narcotics and other crimes are still relatively high. So it can be said that prevention and eradication arrangements that are currently not effective in prevention and pemasannya, because the role of PPATK still waiting for reports from the relevant agencies.